Virtual Velocity Vector-Based Offline Collision-Free Path Planning of Industrial Robotic Manipulator. (22nd September 2015) - Ouyang, Fan; Zhang, Tie
Currently, industrial robotic manipulators are applied in many manufacturing applications. In most cases, an industrial environment is a cluttered and complex one where moving obstacles may exist and hinder the movement of robotic manipulators. Therefore, a robotic manipulator not only has to avoid moving obstacles, but also needs to fulfill the manufacturing requirements of smooth movement in fixed tact time. Thus, this paper proposes a virtual velocity vector-based algorithm of offline collision-free path planning for manipulator arms in a controlled industrial environment. The minimum distance between a manipulator and a moving obstacle can be maintained at an expected value by utilizing our proposed algorithm with established offline collision-free path-planning and trajectory-generating systems. Furthermore, both joint space velocity and Cartesian space velocity of generated time-efficient trajectory are continuous and smooth. In addition, the vector of detour velocity in a 3D environment is determined and depicted. Simulation results indicate that detour velocity can shorten the total task time as well as escaping the local minimal effectively. In summary, our approach can fulfill both safety requirements of collision avoidance of moving obstacles and manufacturing requirements of smooth movement within fixed tact time in an industrial environment.